The Effects of Public Debt Financing: A Multi-state Perspective - Olaoye, Clement Olatunji; Alonge, Funmilayo Bukola (Archives of Business Research, 2022)
This paper investigates the relation between public debt financing and government expenditure. Using year and states fixed effect estimation, we find that the amount owed by federating states propels government spending. While external debts have a significant and positive association with public expenditure, domestic debts have positive effect, though not significantly different from zero, on government expenditure. The study recommends that policymakers in the public sector should widen external debts than domestic debts because its influence governments’ recurrent and capital expenditure.